Penerapan Nilai-Nilai Influencer dalam Pengajaran Bahasa Inggris di SMAN/SMK Negeri Rumbai - Syaifullah; Herdi; Abbas, M. Fadhly Farhy (Journal of Education and Culture, 2024)
English teaching in the city of Pekanbaru in particular has not yet achieved the target expected by the curriculum, creating students who are able to communicate in English. This can be seen in everyday life, generally students who have graduated from high school are still unable to communicate the English they have learned. One of the causal factors is the English teaching methods, techniques or strategies applied by teachers in teaching English in their classes. As one solution to this problem, the author proposes to English teachers to apply the values ​​of influencers to teaching and learning activities in their classes. There are Influencer values ​​that have been found in several previous research results, such as fun, enthusiasm, attention, authenticity, independence, authority, popularity, visibility, creativity, and technological knowledge. Based on the results of interviews with several English teachers from SMAN/SMKN in Rumbai, it was found that they did not fully know and understand the influencer values ​​referred to by previous researchers, and they also did not apply these values ​​in their pursuit of English.